2019
DOI: 10.1098/rsob.180177
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges for the use of induced pluripotent stem cells in modelling neurodegenerative disease

Abstract: Adult-onset neurodegenerative diseases are among the most difficult human health conditions to model for drug development. Most genetic or toxin-induced cell and animal models cannot faithfully recapitulate pathology in disease-relevant cells, making it excessively challenging to explore the potential mechanisms underlying sporadic disease. Patient-derived induced pluripotent stem cells (iPSCs) can be differentiated into disease-relevant neurons, providing an unparalleled platform for in vitro modelling and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 144 publications
(338 reference statements)
0
49
0
Order By: Relevance
“…The progress in tissue engineering technologies during the last years has eminently improved neurodegenerative disease modeling by the generation of 3D cellular complexes resembling human brain tissue termed brain organoids. Brain organoids derived from pluripotent stem cells can effectively model human cortical development and recapitulate its 3D cytoarchitecture; thus, opening a new window of opportunities to further investigate disease pathogenesis in vitro [40,41]. Moreover, the 3D brain organoids can reveal particular disease phenotypes, which are barely observed in 2D culture systems [42].…”
Section: Ipsc-derived Brain Organoid Modelsmentioning
confidence: 99%
“…The progress in tissue engineering technologies during the last years has eminently improved neurodegenerative disease modeling by the generation of 3D cellular complexes resembling human brain tissue termed brain organoids. Brain organoids derived from pluripotent stem cells can effectively model human cortical development and recapitulate its 3D cytoarchitecture; thus, opening a new window of opportunities to further investigate disease pathogenesis in vitro [40,41]. Moreover, the 3D brain organoids can reveal particular disease phenotypes, which are barely observed in 2D culture systems [42].…”
Section: Ipsc-derived Brain Organoid Modelsmentioning
confidence: 99%
“…Luo et al recently showed that in contrast to iPSC-derived neurons, BAM-based iNs are the first cellular neuronal model system displaying this epigenetic hallmark of mature adult neurons [51,142,143]. In vitro generation of patient-specific neurons from iPSCs for modeling diseases of the brain has evolved into an integral part of neuroscience [144][145][146], and employing human iPSC technology to investigate aspects of age-related neurodegenerative diseases in a patient-specific genetic context at a cellular level has yielded important human neuron-specific insights [147][148][149][150]. We expect such criteria to become more and more popular, extending our knowledge of cell identity, and that they will eventually largely replace classical means of neuronal characterization.…”
Section: You Are What You Eat: Metabolic Hallmarks Of In Conversionmentioning
confidence: 99%
“…The direct path to the end: Specifics of iN and their consequences for disease modeling It is primarily due to the inaccessibility of live human brain tissue that most studies on complex age-related neurodegenerative disorders have primarily relied on transgenic animal models that, while yielding important insights, have also revealed limitations regarding transferability to human physiology. In vitro generation of patient-specific neurons from iPSCs for modeling diseases of the brain has evolved into an integral part of neuroscience [144][145][146], and employing human iPSC technology to investigate aspects of age-related neurodegenerative diseases in a patient-specific genetic context at a cellular level has yielded important human neuron-specific insights [147][148][149][150]. However, iPSCbased studies could not shed much new light on the causes of sporadic age-related diseases, because iPSC reprogramming is known to reset the epigenetic state of the cell and erases most of the epigenetic memory, including those that stem from potentially important environmental influences (Fig.…”
Section: Updating Our Criteria To Define Neuronsmentioning
confidence: 99%
“…18,22,77 iPSCs offer the capability to generate specific patient-derived neural subtypes, with CRISPR-Cas9 technology allowing for the genetic modification of these cells. 78 Since neurodegenerative diseases are highly complex, with many different cell types and regions involved, 3D cultures are a step forward in attempting to reproduce the multidimensional environment of the brain and hold an immense potential for modeling neurodegenerative diseases. 74 Figure 8 highlights the entire process from patient to drug, highlighting the enabling technologies of iPSCs combined with CRISPR-Cas9 to both model disease and discover/test new therapeutics.…”
Section: Path Forwardmentioning
confidence: 99%